2023
DOI: 10.15420/cfr.2023.05
|View full text |Cite
|
Sign up to set email alerts
|

Global Public Health Burden of Heart Failure: An Updated Review

Abstract: Heart failure (HF) is a rapidly growing public health issue with an estimated prevalence of 64 million people globally. Although the incidence of HF has stabilised worldwide and seems to be declining in developed countries, the prevalence is increasing due to the ageing of the population, improved survival after MI and improved treatment and survival of patients with HF. Yet, HF remains associated with high mortality and morbidity, poor quality of life and functional capacity, and confers a substantial burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 92 publications
0
40
0
Order By: Relevance
“…The finding reported herein that the risk of adverse outcomes, including all-cause mortality and all-cause hospitalization, was similar in patients with HFrEF, HFmrEF, and HFpEF, even after adjusting for confounders, is in contrast to existing literature which primarily supports that patients with HFrEF have worse clinical outcomes. 7,12,13 TRANSFORM-HF, owing to its pragmatic design and method for end point ascertainment, prespecified the use of all-cause death and allcause hospitalization, alone and in combination, as its end points. 8 Previous HF studies have mainly focused on cardiovascular mortality and HF hospitalization and have shown that HFrEF is associated with an increased risk of these compared with HFpEF, which is, in part at least, counterbalanced by the proportionally lower risk of noncardiovascular mortality and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding reported herein that the risk of adverse outcomes, including all-cause mortality and all-cause hospitalization, was similar in patients with HFrEF, HFmrEF, and HFpEF, even after adjusting for confounders, is in contrast to existing literature which primarily supports that patients with HFrEF have worse clinical outcomes. 7,12,13 TRANSFORM-HF, owing to its pragmatic design and method for end point ascertainment, prespecified the use of all-cause death and allcause hospitalization, alone and in combination, as its end points. 8 Previous HF studies have mainly focused on cardiovascular mortality and HF hospitalization and have shown that HFrEF is associated with an increased risk of these compared with HFpEF, which is, in part at least, counterbalanced by the proportionally lower risk of noncardiovascular mortality and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous HF studies have mainly focused on cardiovascular mortality and HF hospitalization and have shown that HFrEF is associated with an increased risk of these compared with HFpEF, which is, in part at least, counterbalanced by the proportionally lower risk of noncardiovascular mortality and hospitalization. 12 Thus, a different study design, focused on cardiovascular or HF-specific outcomes, may have produced higher incidence of events for patients with HFrEF. Moreover, HF is a heterogeneous clinical syndrome and the LVEF cutoffs and criteria used to define these groups have considerably changed over the past years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the rising global burden of heart failure (HF) and the availability of evidencebased therapies for preventing and slowing the progression of the disease, there is a lack of a reliable approach for identifying individuals at the highest risk for developing HF. 1,2 Due to this absence of an established and accessible screening strategy, patients often suffer the consequences of delayed diagnosis, including clinical HF, frequent hospitalizations, and premature mortality. [3][4][5] Identifying individuals most likely to develop future HF can alleviate these risks with early initiation of low-cost medical therapies that have been proven in clinical practice guidelines to modify the trajectory of the disease, reducing both the risk for incident clinical HF and improving life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…
This article refers to 'Effect of a transitional care model following hospitalization for heart failure: 3-year outcomes of the Patient-Centered Care Transitions in Heart Failure (PACT-HF) randomized controlled trial' by T. Averbuch et al, published in this issue on pages 652-660.Heart failure (HF) currently affects over 64 million people worldwide, placing a growing burden on health care systems due to the costs of disease management and downstream complications. 1,2 Contemporary observational studies have highlighted the ongoing underutilization of guideline-directed medical therapy (GDMT) as a driving factor for HF morbidity and mortality, while concurrently emphasizing gaps in knowledge on reducing readmissions and morbidity via medication adherence optimization. For instance, the CHAMP-HF study identified significant percentages of outpatient HF patients that were not on eligible GDMT classes, and more concerningly found minimal improvement in medication initiation and titration during follow-up.
…”
mentioning
confidence: 99%